Algeria - France Relations in the Perspective of Financial History - Özgenur Özyalçın (Maliye Çalışmaları Dergisi)
Algeria is the largest country in Africa by surface area and has important Mediterranean ports and extremely rich natural resources. Its geopolitical location and strength of resource have made Algeria the cradle of different cultures and civilizations throughout history. The French occupation left bloody traces on the political and financial history of the country, and The French influence is still observable today in many areas, especially in the culture, language, and political structuring. Therefore, the history of the country and the people’s spirit of freedom need to be examined in order to Algeria’s current fiscal system. After the AlgerianWar of Independence, The Algerian State declared the goal of “developing the country by making it an industrial country by making maximum use of its natural resources and raising the welfare and cultural level of the people in this way”. (Erinç, 1993, s. 494-497) This aim indicates that the utilization of the country’s resources has been seriously delayed. All foreign-owned companies, industrial facilities, businesses, and agricultural areas had been nationalized for this purpose, and all economic and social planning and foreign trade, major industrial facilities, banks, credit institutions, transportation, communication equipment, and economic sectors are entirely under the control of the State of Algeria. Past experiences that had made Algeria’s national identity invisible have laid the groundwork for conservative policies nowadays in favor of state control.